IMPLEMENTASI MODEL DISCOVERY LEARNING BERBASIS MEDIA GAMBAR DALAM MENINGKATKAN KECERDASAN EKOLOGIS SISWA SEKOLAH DASAR - Ema Rahmawati; Galih Dani Septiyan Rahayu (COLLASE (Creative of Learning Students Elementary Education), 2021)
The study was intended to increase the ecological intelligence of the cisintok class iv student based on media pictures in the implementation of the discovery learning model. Researchers applying the discovery learning model in class iv are expected to give students active, creative and enjoyable learning. As for picture media, it is necessary for students to make learning more interesting and to increase student study interest. The metedology used is a qualitative description with a class iv SDN cisintok subject, 2019/2020 year of 30 students. The research has the four components of planning, action, observation and reflection. The use of instruments is an observation sheet, an angkette sheet, an interview sheet. The data-analysis techniques in this study use qualitative descriptive techniques. This research's success indicator is that by increasing the student's ecological intelligence of garbage processing, 83 percent of the students achieve their assigned KKM. Results from this study showed that the use of media pictures with the discovery learning model proved to be able to increase the ecological intelligence of the west bandung district iv. Keywords: ecological intelligence, media images, garbage processing materials, the discovery learning model